M-health with cardiac rehabilitation improves functional capacity: A systematic review with meta-analysis - Pierucci, Alessandro; de Almeida, Nathália Soares; Lemes, Ítalo Ribeiro [UNESP]; Milanez, Vinicíus Flávio; Oliveira, Crystian Bitencourt; Kretli Winkelströter, Lizziane; de Abreu, Marilda Aparecida Milanez Morgado; Nakagaki, Wilson Romero; Toledo, Ana Clara Campagnolo Gonçalves (Elsevier, 2025)
Background and objective: In this systematic review and meta-analysis, we compared the effectiveness of the combined m-health and a cardiac rehabilitation program (CRP) and of CRP alone on functional capacity, adherence to CRP, and management of cardiovascular risk factors in cardiac patients. Methods: Medline, EMBASE, Central, PEDro, and SPORTDiscus were searched, from inception until July 2020, for randomized controlled trials (RCTs) comparing the m-health with CRP combination with CRP alone for adults with heart disease. The PEDro scale and GRADE approach was used to assess methodological and overall quality, respectively. Pooled estimates were calculated using a random-effects model to obtain the mean difference (MD) or standardized mean difference (SMD), and their respective 95 % confidence intervals (95 %CIs). Results: Twenty-two RCTs were eligible. The median risk-of-bias was 6.5/10. CRP with the m-Health intervention was more effective than CRP alone in improving VO2peak (MD: 1.02 95 %CI 0.50 -1.54) at short-term, and at medium-term follow-up (MD: 0.97, 95 %CI: 0.04 - 1.90. Similarly, CRP and m-Health were superior to CRP alone in increasing self-reported physical activity at short-term (SMD: 0.98, 95 %CI: 0.65 - 1.32] but not at medium-term follow-up (SMD: 0.18, 95 %CI:0.01 to 0.36). Furthermore, supervision of CRP with the m-Health intervention at short-term follow-up and M-Health and semi-supervised CRP – medium-term were more effective in improving VO2peak respectively (MD: 1.01, 95 %CI: 0.38‒1.64), (MD: 1.49, 95 %CI: 0.09, 2.89), and self-reported physical activity than supervised CRP at short-term (SMD: 0.98, 95 %CI: 0.65‒1.32) medium-term follow-ups (MD: 0.29 95 %CI: 0.12, 0.45]. Conclusion: Our review found high-quality evidence that m-health interventions combined with CRP was more effective than CRP alone in improving cardiorespiratory fitness, at the short and medium terms follow-up.
Keywords: cardiorespiratory fitness; Exercise; Health app; m-health; Physical fitness; Randomized controlled trials; Rehabilitation program; Telehealth; VO2peak